Evaluation of the content of trace elements in the aerial and underground biomass of perennial grasses of the genus Miscanthus - Stypczyńska, Zofia; Dziamski, Andrzej; Jaworska, Hanna; Dąbkowska-Naskręt, Halina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The content of lead, zinc, copper, nickel and chromium in the aerial and underground parts of M. sinensis from eleven years old plantation and M. sacchariflorus and M. giganteus from nine years old plantations were analysed in order to recognize what organs of the plant play the most important function as a metal accumulator. It was found that in the aboveground parts, lead, zinc and copper were accumulated mostly in leaves and nickel and chromium in stems of the studied species. In underground plant parts, especially in roots, zinc, copper and nickel were most abundantly accumulated, while rhizomes accumulated higher amounts of lead and chromium. The content of lead, zinc and copper was definitely lower in those plant organs than their content in soil. The content of nickel and chromium, on the other hand, showed the opposite dependence. A similar capacity for uptaking trace elements from soil was observed for M. sacchariflorus and M. giganteus, while M. sinensis it was much lower, which is confirmed by the values of the bioaccumulation factors. The translocation factor for trace metals in the studied grass species indicated great translocation of lead and nickel from the roots to rhizomes, and that of zinc to aboveground parts.
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 141-151
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma